(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides information about several games that are increasingly disappearing among children. The main goal was to study and restore their description and definition. Relying on the comparative-historical method, data was studied during material collection, observation and interview. As a result, information about their naming and history of origin was clarified. Special attention was paid to the procedure, conditions and main goals and objectives of these games. Folk games prepare children for life in all aspects. During the game, their eyes, ears, sense of touch and hearing are sharpened. Mentally, it increases the ability to get the right target, plan, and plan by teaching it to the book. It was concluded that it forms the ability to deal with many people.